On continual interpolation nodes for operators in linear topological spaces - Kashpur, O. F.; Makarov, V. L.; Khlobystov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish conditions for the existence of continual nodes for interpolation polynomials of the integral type. This result is generalized to the case of multivariable operators. Some examples of these interpolants are analyzed.